2013
DOI: 10.1159/000343523
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Male Reproductive Surgery: Robotic-Assisted Vasovasostomy

Abstract: It is estimated that 3–6% of all vasectomised men request vasectomy reversal for different reasons. Microsurgical vasovasostomy is the gold standard technique of vasectomy reversal. However, the microsurgical technique is time-consuming and challenging to most urological surgeons. Therefore, alternative methods of vasal anastomosis have been studied including robotic-assisted vasovasostomy. This review discusses the feasibility and practice of robotic-assisted vasovasostomy. Based on the available studies robo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The result showed a significant association of knowledge of males with their selected variables. The calculated p value of males and females with selected variables of knowledge and attitude was nonsignificant which showed that there was no association between the level of knowledge and attitude of males and females towards tubectomy and vasectomy [8]. Conclusion: It was concluded that Knowledge of the males and females regarding tubectomy and vasectomy was in average and Attitude was moderately favourable [20].…”
Section: A the Influence Of Knowledge Factor With The Participation M...mentioning
confidence: 86%
See 1 more Smart Citation
“…The result showed a significant association of knowledge of males with their selected variables. The calculated p value of males and females with selected variables of knowledge and attitude was nonsignificant which showed that there was no association between the level of knowledge and attitude of males and females towards tubectomy and vasectomy [8]. Conclusion: It was concluded that Knowledge of the males and females regarding tubectomy and vasectomy was in average and Attitude was moderately favourable [20].…”
Section: A the Influence Of Knowledge Factor With The Participation M...mentioning
confidence: 86%
“…The cause of the low participation of men in the MOP method of family planning is that there are still many people who do not know about the existence of contraception for men other than condoms, making men ultimately unable to participate directly in the use of contraception, but also because of negative attitudes and thoughts about male contraception, thinking that family planning is a duty [6] [7]. women are not the responsibility of men even though the regulation of pregnancy and family welfare is a shared responsibility, not to mention the bad stigma that grows in society about vasectomy which makes people think that vasectomy is the same as castration, vasectomy interferes with ejaculation and erection as well as sexual relations, wife support also many wives are worried that if their husbands use vasectomy contraception, their husbands can have sexual relations with other people without fear of getting pregnant [3] [8].…”
mentioning
confidence: 99%
“…Therefore, it was considered that a surgeon who is trained in both RAVV and MVV is best suited for vasal anastomosis in order to shorten the operative time and improve the patency rate. Additionally, the learning curve for robotic surgery seems to be shorter than for microsurgery and previous experience in microsurgery does not affect the curve . This advantage is a boon to urologists who lack opportunities for microsurgery.…”
Section: New Inventions In Microscopic Vasovasostomy and Vasoepididymmentioning
confidence: 99%
“…Additionally, the learning curve for robotic surgery seems to be shorter than for microsurgery and previous experience in microsurgery does not affect the curve. 63,64 This advantage is a boon to urologists who lack opportunities for microsurgery.…”
Section: Robot-assisted Vasovasostomy and Vasoepididymostomymentioning
confidence: 99%
“…However, the reported rates of vasal patency and pregnancy with this new and very expensive surgical technique are similar to that of microsurgical vasovasostomy. Given these results and the expense of robot-assisted surgery, the traditional microsurgical approach to vasal reconstruction is preferred [46,49].…”
mentioning
confidence: 99%